Equipment, staffing, and provision of radiotherapy in Lombardy, Italy: Results of three surveys performed between 2012 and 2016. Issue 5 (October 2018) - Palazzi, Mauro F.; Soatti, Carlo; Jereczek-Fossa, Barbara A.; Cazzaniga, Luigi F.; Antognoni, Paolo; Gardani, Gianstefano; Amadori, Marcello; Baio, Ambrogia; Beltramo, Giancarlo; Bignardi, Mario; Bracelli, Stefano; Buffoli, Alberto; et al.
Introduction: Several efforts are being implemented at the European level to measure provision of up-to-date radiation treatments across the continent. Methods: A snapshot survey involving all radiation oncology centers within Lombardy, Italy, was performed in 2012 and repeated in 2014 and 2016, in cooperation with regional governmental officers. Centers were asked to provide detailed information concerning all individual patients being treated on the index day, and to report data on available local resources. Results: We observed an increase in the number of centers and of megavoltage units (MVU) (from 76 to 87, i.e., 8.7 MVU per million inhabitants in 2016). Mean number of MVU per center was 2.5. Average age of MVU increased from 5.3 to 7.5 years and patients on the waiting list also increased. Conformal 3D radiotherapy (RT) treatments decreased from 56% to 42% and were progressively replaced by intensity-modulated RT treatments (from 39% to 49%). Waiting times were overall satisfactory. Radiation oncologists treated on average 152 and radiation therapists 100 RT courses per year. Average reimbursement per course was €4, 879 (range €2, 476–€8, 014). Conclusions: The methodology of snapshot survey proved feasible and provided valuable information about radiation oncology provision and accessibility in Lombardy.